Inflammasome Inhibition Prevents Motor Deficit and Cerebellar Degeneration Induced by Chronic Methamphetamine Administration - Ding, Jiuyang; Shen, Lingyi; Ye, Yuanliang; Hu, Shanshan; Ren, Zheng; Liu, Ting; Dai, Jialin; Li, Zhu; Wang, Jiawen; Luo, Ya; Zhang, Qiaojun; Zhang, Xiali; et al. (Frontiers in Molecular Neuroscience, 2022)
Methamphetamine (METH), a psychostimulant, has the potential to cause neurodegeneration by targeting the cerebrum and cerebellum. It has been suggested that the NLRP3 inflammasome may be responsible for the neurotoxicity caused by METH. However, the role of NLRP3 in METH-induced cerebellar Purkinje cell (PC) degeneration and the underlying mechanism remain elusive. This study aims to determine the consequences of NLRP3 modulation and the underlying mechanism of chronic METH-induced cerebellar PC degeneration. In METH mice models, increased NLRP3 expression, PC degeneration, myelin sheath destruction, axon degeneration, glial cell activation, and motor coordination impairment were observed. Using the NLRP3 inhibitor MCC950, we found that inhibiting NLRP3 alleviated the above-mentioned motor deficits and cerebellar pathologies. Furthermore, decreased mature IL-1β expression mediated by Caspase 1 in the cerebellum may be associated with the neuroprotective effects of NLRP3 inflammasome inhibition. Collectively, these findings suggest that mature IL-1β secretion mediated by NLRP3-ASC-Caspase 1 may be a critical step in METH-induced cerebellar degeneration and highlight the neuroprotective properties of inflammasome inhibition in cerebellar degeneration.